2018
DOI: 10.1016/j.ymben.2018.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Pichia pastoris

Abstract: Besides its use for efficient production of recombinant proteins the methylotrophic yeast Pichia pastoris (syn. Komagataella spp.) has been increasingly employed as a platform to produce metabolites of varying origin. We summarize here the impressive methodological developments of the last years to model and analyze the metabolism of P. pastoris, and to engineer its genome and metabolic pathways. Efficient methods to insert, modify or delete genes via homologous recombination and CRISPR/Cas9, supported by modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
109
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 188 publications
(116 citation statements)
references
References 186 publications
0
109
0
7
Order By: Relevance
“…Over the past three decades, the methylotrophic yeasts Pichia pastoris (Pp), Hansenula polymorpha (Hp), Candida boidinii (Cb) and Pichia methanolica (Pm) have emerged as powerful alternatives, enabling high cell density fermentation and simple, pure secretion of heterologous proteins (Gellissen 2000;Hartner and Glieder 2006;Yurimoto et al 2011;). The two Pichia species and H. polymorpha have phylogenetically been reassigned as Komagataella and Ogataea species, respectively resulting in the formal names Komagataella phaffii, Ogataea polymorpha, and Ogataea methanolica (Peña et al 2018). Amongst these four methylotrophic yeasts, P. pastoris is most commonly applied for heterologous protein production, even surpassing S. cerevisiae according to a recent literature survey (Bill 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past three decades, the methylotrophic yeasts Pichia pastoris (Pp), Hansenula polymorpha (Hp), Candida boidinii (Cb) and Pichia methanolica (Pm) have emerged as powerful alternatives, enabling high cell density fermentation and simple, pure secretion of heterologous proteins (Gellissen 2000;Hartner and Glieder 2006;Yurimoto et al 2011;). The two Pichia species and H. polymorpha have phylogenetically been reassigned as Komagataella and Ogataea species, respectively resulting in the formal names Komagataella phaffii, Ogataea polymorpha, and Ogataea methanolica (Peña et al 2018). Amongst these four methylotrophic yeasts, P. pastoris is most commonly applied for heterologous protein production, even surpassing S. cerevisiae according to a recent literature survey (Bill 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is a widely used industrial microorganism and has several other advantages over other eukaryotic and prokaryotic expression hosts, such as simple medium, easy genetic manipulation, diverse posttranslational modifications, less extensive glycosylation, good secretion ability (Safder et al, 2018). Till date, a variety of proteins, small molecule drugs, and food additives have been synthesized using P. pastoris as the chassis (Peña et al, 2018;Safder et al, 2018).…”
Section: Hatzimanikatismentioning
confidence: 99%
“…In contrast to its well‐known function as a protein expression system, the potential of P. pastoris as a cell factory for the production of chemicals has been largely underestimated. Nevertheless, increasing number of studies reported using P. pastoris as a microbial cell factory for the production of chemicals either via biocatalysis or more recently via fermentation . This paper aims to outline the major progress made in recent years toward developing P. pastoris as an efficient yeast cell factory with emphasis on its role as a whole‐cell catalyst for chemical production.…”
Section: Introductionmentioning
confidence: 99%